Expression of the 12-Oxophytodienoic Acid 10,11-Reductase Gene in the Compatible Interaction between Pea and Fungal Pathogen - Ishiga, Y.; Funato, A.; Tachiki, T.; Toyoda, K.; Shiraishi, T.; Yamada, T.; Ichinose, Y.
Suppressors produced by Mycosphaerella pinodes are glycopeptides to block pea defense responses induced by elicitors. A clone, S64, was isolated as cDNA for suppressorinducible gene from pea epicotyls. The treatment of pea epicotyls with suppressor alone induced an increase of S64 mRNA within 1 h, and it reached a maximum level at 3 h after treatment. The induction was not affected by application of the elicitor, indicating that the suppressor has a dominant action to regulate S64 gene expression. S64 was also induced by inoculation with a virulent pathogen, M. pinodes, but not by inoculation with a non-pathogen, Ascochyta rabiei, nor by treatment with fungal elicitor. The deduced structure of S64 showed high homology to 12- oxophytodienoic acid reductase (OPR)in Arabidopsis thaliana. A recombinant protein derived from S64 had OPR activity, suggesting compatibility-specific activation of the octadecanoid pathway in plants. Treatment with jasmonic acid (JA)or methyl jasmonic acid, end products of the octadecanoid pathway, inhibited the elicitor-induced accumulation of PAL mRNA in pea. These results indicate that the suppressor-induced S64 gene expression leads to the production of JA or related compounds, which might contribute to the establishment of compatibility by inhibiting the phenylpropanoid biosynthetic pathway.
Keywords: JASMONIC ACID; OXOPHYTODIENOIC ACID REDUCTASE; SUPPRESSOR